PV panels Rs parasitic resistance degradation estimation by means of the MPPT controller modified operation: the M ‐factor calculation. Issue 22 (25th September 2020) - Sánchez‐Pacheco, F.J.; Heredia‐Larrubia, J.R.; Petrone, G.; Sidrach‐de‐Cardona, M.
Abstract : This Letter describes a method to quantify online and in real‐time, the level of degrading of the series parasitic resistance R s of a photovoltaic (PV) panel. This method aims to obtain the herein proposed M ‐factor, which results from the calculation of the slopes of the I–V curve in the boundaries of its maximum power‐point. For this purpose, the slight modification of the maximum power‐point tracker controller' perturb and observe algorithm is required. This procedure can be easily integrated into its firmware with no additional costs. The M ‐factor calculation is performed instantaneously and since no disconnection is required, no significant power losses are produced.